Master of ICT at AeU - The, Sun (The Sun, 2018)
Asia e University (AeU) is a premier open and distance learning institution in Asia and has set up a university in Malaysia. It is founded on innovation and technology and has its focus on the digital frontier. Among its many programmes is the Master of Information and Communication Technology (MICTM). The degree programme is structured to equip students with interdisciplinary skills. It offers a reliable link between the dynamics of technology and management in business. It is recommended for IT professionals who will improve their leadership skills and techniques and develop a more strategic approach to deal with today's tech-savvy organisations.